2015
DOI: 10.1155/2015/925167
|View full text |Cite
|
Sign up to set email alerts
|

The Cardioprotective Effects of Hydrogen Sulfide in Heart Diseases: From Molecular Mechanisms to Therapeutic Potential

Abstract: Hydrogen sulfide (H2S) is now recognized as a third gaseous mediator along with nitric oxide (NO) and carbon monoxide (CO), though it was originally considered as a malodorous and toxic gas. H2S is produced endogenously from cysteine by three enzymes in mammalian tissues. An increasing body of evidence suggests the involvement of H2S in different physiological and pathological processes. Recent studies have shown that H2S has the potential to protect the heart against myocardial infarction, arrhythmia, hypertr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 126 publications
1
89
0
7
Order By: Relevance
“…Subsequently, a plethora of investigations were performed on potential roles of H 2 S in cardiovascular disease (CVD), which revealed that physiological levels of H 2 S have a pivotal role in maintaining cardiac function, and an exogenous supply of H 2 S has the potential to ameliorate heart failure in rodents. Empirical studies elucidated several potential mechanisms of H 2 S-mediated cardioprotection in different models of heart failure (21,117,123,128,150). However, regulation of H 2 S functions during heart failure is not completely understood.…”
mentioning
confidence: 99%
“…Subsequently, a plethora of investigations were performed on potential roles of H 2 S in cardiovascular disease (CVD), which revealed that physiological levels of H 2 S have a pivotal role in maintaining cardiac function, and an exogenous supply of H 2 S has the potential to ameliorate heart failure in rodents. Empirical studies elucidated several potential mechanisms of H 2 S-mediated cardioprotection in different models of heart failure (21,117,123,128,150). However, regulation of H 2 S functions during heart failure is not completely understood.…”
mentioning
confidence: 99%
“…* P <0.05 relative to adult animals (100%). # P <0.05 relative to old rats, which were not treated with NaHS and homogenate of the heart from old rats should be separately noted, as the latter serves as a regulator of NO synthesis and powerful cardio-and vasoprotector [7][8][9][10]. The injection of exogenic hydrogen sulfide donor, NaHS, significantly increased the amount of H 2 S both in the mitochondria and homogenate of the heart from old animals, which was accompanied by a significant inhibition of both oxidative and nitrosative stress.…”
Section: Resultsmentioning
confidence: 99%
“…This effect is due to antioxidant, anti-inflammatory properties of the gas, as well as its ability to regulate the constitutive de novo synthesis of NO [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a growing body of evidence has shown that H 2 S is a critical regulator of cardiac functions and plays a protective role in the pathogenesis and development of heart diseases such as myocardial infarction, arrhythmia, hypertrophy, fibrosis, and I/R injury. 2,3) Some mechanisms have been proposed by which H2S exerts cardioprotective effects, including reduction of apoptosis, preservation of mitochondrial function, anti-inflammatory responses, and angiogenic actions. [4][5][6][7] However, the specific mechanism of cardioprotection mediated by H 2 S in I/R injury is still largely unknown.…”
Section: Hydrogen Sulfide a Potential Cardioprotective Gas Activatinmentioning
confidence: 99%